Language for Specific Purposes in the Framework of Criminal Justice and Security - Kompara Lukančič, Mojca (2022)
The scientific monograph is oriented towards LSP for the field of criminal justice and security studies and also focuses on subfields, namely police, law, security, administration, etc. The monograph contains contributions from the field of criminal justice and security studies prepared by Slovenian and foreign authors, namely Jelena Gugić from the University of Pula, Mojca Kompara Lukančič from the University of Maribor, Nives Lenassi from the University of Ljubljana, Dragoslava Mićović from the University of Belgrade, Eva Podovšovnik from the University of Primorska, Jasna Potočnik Topler from the University of Maribor, Vanja Slavuj from the University of Rijeka, and Tilen Smajla from the University of Maribor. The work offers an insight into English and Italian through the prism of contents that focus on the language for specific purpose for the field of criminal justice and security.
Keywords: the English language; the Italian language; criminal justice and security; terminology; LSP